Molecular medicine : an introductory text - Trent, R. J. (Elsevier Academic Press, 2005)
Molecular medicine is the application of gene or DNA based knowledge to the modern practice of medicine. This book provides contemporary insights into how the genetic revolution is influencing medical thinking and practice on a broad front including clinical medicine, innovative therapies and forensic medicine.